PERUBAHAN FISIK SPASIAL KAWASAN PINGGIRAN MEMARGINALKAN KOMUNITAS LOKAL (KASUS KOTA BARU METRO TANJUNG BUNGA, MAKASSAR) - Batara Surya (TATALOKA, 2011)
Research conducted on the development of new urban Metro Tanjung Bunga to analyze spatial physical changes in work as a determinant of social formation changes, in the Metro Tanjung Bunga area, using qualitative approaches and quantitative approaches. Data obtained from a number of good local community informants from community leaders and the respondent. Spatial physical changes that take place very quickly encourage the acceleration of development, starting with the development of new functions, encourage the entry of migrants in infiltrative and expansive. The changes of a single social formation to double formation inside there precapitalist social formations and social formations of capitalism suggests that the coexistence of two types of social formations in the mastery of space on the reproductive development of new urban areas are not always mutual interrelation and harmony, so impact to the marginalization of local communities.